Life Writing in the Colonial Archives: The Case of Nnamdi Azikiwe (1904–1996) of Nigeria. Issue 3 (2nd July 2016) - Newell, Stephanie
ABSTRACT: Commentators on Europe's colonial archives often highlight the lack of coherence to be found in official and national repositories. Even within a single file, the archives do not simply, or only, yield evidence about imperial intentions and colonial subjects in Europe's diverse territories. Focusing on secret files compiled in the 1930s and 1940s around the activities of the prominent Nigerian newspaper editor and later first president of Nigeria, Nnamdi Azikiwe (1904–1996), this article argues that Colonial Office archives reveal the tensions between imperialism as a hegemonic ideology and the diverse practices of individuals, including colonial governors, civil servants in London, and their critics in the colonial public sphere. The article shows how Azikiwe's biography was produced by spies and informants in Nigeria, and by civil servants at the Colonial Office, but that Azikiwe himself cleverly exploited the meticulous record-keeping procedures in Whitehall to insert his political autobiography into the files for posterity.